Between entrepreneurs and workers: Cleavages and compromises in rationales and policy solutions regarding 'dependent contractors'. (November 2022) - Florin, Louis; Pichault, François
The emergence of dependent contractors challenges the existing institutions regarding social protection and labour regulation. This article aims at identifying the political narratives that explain the emergence of New Forms of Employment (NFE) and dependent contracting along with the policy solutions proposed by the social partners at the EU and international level. By analysing policy documents from the social partners through the lens of a qualitative version of the Narrative Policy Framework (NPF), the authors indentify two distinct narratives – 'devaluation of work' and 'entrepreneurship and flexibility'. The authors show how these rationales lead to various policy solutions and identify oppositions and possible compromise.